The final, Late Campanian – Early Maastrichtian stage of Micraster and Isomicraster (Echinoidea, Spatangoida) development - Kalyakin, Evgeniy Aleksandrovich (Известия Саратовского университета. Новая серия: Серия Науки о Земле, 2025)
The final, late Campanian – early Maastrichtian stage of development of echinoids Micraster and Isomicraster, was studied based on extensive material from the Upper Cretaceous sediments of the North Caucasus, Mangyshlak, Kopetdag, Volga and Transvolga regions. The changes in the complex of morphological characters in the youngest species, which are predominantly connected with variability in the structure of the oral surface of the test, considered in detail. It is shown that similar morphological changes occurred in different representatives of these genera at approximately the same time in different territories. The stratigraphic significance of Micraster brongniarti Hebert and M. grimmensis Nietsch was assessed. Conclusions about possible paths of distribution of M. grimmensis Nietsch in the Campanian – Maastrichtian water areas of the European, Mediterranean and Central Asian palaeobiogeographical areas were drawn. In total material from three collections of 110 specimens was studied.